Immune cell census in murine atherosclerosis: cytometry by time of flight illuminates vascular myeloid cell diversity - Cole, JE; Park, I; Kassiteridi, C; Ahern, D; Goddard, M; Green, P; Maffia, P; Monaco, C (Oxford University Press, 2018)
Aims: Atherosclerosis is characterised by the abundant infiltration of myeloid cells starting at early stages of disease. Myeloid cells are key players in vascular immunity during atherogenesis. However, the subsets of vascular myeloid cells have eluded resolution due to shared marker expression and atypical heterogeneity in vascular tissues. We applied the high-dimensionality of mass cytometry to the study of myeloid cell subsets in atherosclerosis. Methods and Results: Apolipoprotein E-deficient (ApoE-/-) mice were fed a chow or a high fat (western) diet for 12 weeks. Single cell aortic preparations were probed with a panel of 35 metal-conjugated antibodies using Cytometry by time of flight (CyTOF). Clustering of marker expression on live CD45+ cells from the aortas of ApoE-/- mice identified 13 broad populations of leucocytes. Monocyte, macrophage, type 1 and type 2 conventional dendritic cell (cDC1 and cDC2), plasmacytoid dendritic cell (pDC), neutrophil, eosinophil, B cell, CD4+ and CD8+ T cell, γδ T cell, natural killer (NK) cell and innate lymphoid (ILC) cell populations accounted for approximately 95% of the live CD45+ aortic cells. Automated clustering algorithms applied to the Lin-CD11blo-hi cells revealed 20 clusters of myeloid cells. Comparison between chow and high fat fed animals revealed increases in monocytes (both Ly6C+ and Ly6C-), pDC and a CD11c+ macrophage subset with high fat feeding. Concomitantly, the proportions of CD206+ CD169+ subsets of macrophages were significantly reduced as were cDC2. Conclusions: A CyTOF-based comprehensive mapping of the immune cell subsets within atherosclerotic aortas from ApoE-/- mice offers tools for myeloid cell discrimination within the vascular compartment and it reveals that high fat feeding skews the myeloid cell repertoire towards inflammatory monocyte-macrophage populations rather than resident macrophage phenotypes and cDC2 during atherogenesis.